PTU-162 "coeliac disease screening in '2 week wait' patients: biopsy or serology?". (22nd June 2015) - Kotha, S; McLaren, K; Holohan, C; McNair, A
Abstract : Introduction: Patients with iron deficiency anaemia (IDA) or weight loss are usually referred to gastroenterology services through the 2 week wait (2ww) referral pathway. When these patients undergo an oesophagogastroduodenoscopy (OGD) it is common practice to take biopsies from the second part of the duodenum (D2) to exclude coeliac disease. Both BSG (British Society of Gastroenterology) and NICE (National Institute for Health and care Excellence) guidelines recommend that patients with suspected coeliac disease should be screened with serology initially. If coeliac serology is negative then small bowel biopsies are generally not necessary. Despite this D2 are routinely taken which results in an increased workload and cost. Method: The aim of this study was to determine if D2 biopsies were necessary and cost effective in patients with IDA or weight loss referred on the 2ww pathway. We analysed retrospective data collected from the endoscopy database (Adam) at Queen Elizabeth Hospital for 400 patients referred through 2ww pathway (200 for IDA and 200 for weight loss) who underwent an OGD. Demographic data, histological findings and cost of analysing histology were evaluated. Results: Of the 200 IDA patients who had D2 biopsy during the study period, 2 patients were excluded (1 had a prior diagnosis of coeliac and 1 did not have histology results on our system). 3 patients had villous atrophy (serology was not checked in 1 patient, 2 had positive serology). The overall pick up rate for significant pathology on D2 biopsies for IDA was 1.5% With D2 biopsy for weight loss, 2 patients were excluded (no histology results was available), 2 patients had villous atrophy (serology was not checked in 1 patient and was negative in 1 patient who had a low IgA), 1 patient had Crohn's disease on histology. The overall pick up rate for significant pathology on D2 biopsies for weight loss was 1.0%. The cumulative cost of analysing these biopsies was £ 13, 440 (£33.6/biopsy). Conclusion: Overall only a single patient with villous atrophy would have been missed if celiac serology was used in place of D2 biopsies. The cost of performing these biopsies is considerable and burdens the histopathology with large numbers of specimens that have to be processed urgently. Coeliac serology should therefore be done in place of D2 biopsies in 2ww patients undergoing OGD. Disclosure of interest: None Declared.